Parental Psychological Absence among Basic Education Students (College of Basic Education Research Journal, 2025)
Aim of  current study was to investigate  level of psychological absence among  participants,  extent of psychological absence according to  gender variable, and  degree of psychological absence attributed to each parent (father and mother) as perceived by  students (i.e.  sample). To achieve  study’s objectives, a psychological absence scale was developed, consisting of four domains: (psychological support, social communication, gender stereotyping, and socio-moral-educational concepts). Initial scale included 51 items, each with three response options (Always, Sometimes, Never). To ensure  validity of the instrument, it was reviewed by a panel of psychology experts. Based on their feedback, 11 items were eliminated, resulting in a final scale of 40 valid items that received over 80% agreement among experts. Reliability of  scale was confirmed through  test-retest method, yielding a reliability coefficient of 0.87. Instrument was administered to a sample of 150 students; after excluding invalid responses,  final sample comprised 146 students (78 females and 68 males). Statistical analysis of  data revealed that students in basic education schools experienced a sense of psychological absence of their parents. Significant gender differences were found, with males reporting higher levels of psychological absence. Further, analysis showed that psychological absence related to fathers among male students was not statistically significant, whereas psychological absence related to mothers was statistically significant. Considering these findings,  researchers proposed a number of conclusions, suggestions, and recommendations.